Evaluation of Quality Failures in the Production Process Using the Seven Tools and Failure Mode and Effect Analysis (FMEA): Evaluasi Kegagalan Kualitas Proses Produksi Menggunakan Metode Seventools dan Failure Mode and Effect Analysis (FMEA) - Achmad Luqman Hakim; Wiwin Widiasih (PROZIMA (Productivity, Optimization and Manufacturing System Engineering), 2025)
CV. Simetri Utama, a manufacturer of frozen shrimp molds, has two dominant types of defects: imperfect codes and uneven shapes. Based on the research findings, the product defect rate exceeds the company standard of 3%. This study aims to identify the types of defects, analyze the contributing factors and impacts of failures, and propose improvement recommendations to minimize the risks of product defects. The methods used are the Seven Tools and Failure Mode and Effect Analysis (FMEA). The Seven Tools are applied to analyze and resolve issues related to product quality. The results show that uneven shape defects account for 54.55%, making them the most dominant, followed by imperfect code defects at 45.45%. Failure Mode and Effect Analysis (FMEA) is utilized to determine the priority level of risks through the assessment of Severity, Occurrence, and Detection. The main contributing factors include improper tool and zero-point settings, incorrect tool selection, suboptimal parameters, as well as environmental and machine conditions. Based on the Risk Priority Number (RPN) generated through the FMEA approach, six failure types are prioritized for evaluation, namely finishing, roughing, tool offset adjustment, semi-finishing, zero-point setting, with tool offset adjustment being the top priority for improvement. The application of the Seven Tools and FMEA methods is expected to reduce the risks of identified potential failures, thereby lowering the defect rate and continuously improving product quality